Influence of the Zinc Tin Oxide Nanoparticle proportions on the Optical properties prepared by the laser Method - Aissa R. Safah; Zuheer N. Majeed; Kasim H. Mohmood (Tikrit Journal of Pure Science)
In this research, the pulse laser deposition method was used by the PLD Nd:YAG wavelength laser nm1064λ = to precipitate thin films of pure zinc oxide and tin-like oxide with different weight ratios (0.2 , 0.4)kg were deposited on glass bases in order to study the effect of annealing at a degree 573k and deformation of some physical properties of zinc nanoparticle oxide films. X-ray diffraction measurements of pure and tainted oxide films of different proportions (0.2, 0.4)kg in tin indicated that these films possess a multi-crystal line structure, of hexagonal type. The topographical properties of the prepared membrane surfaces were studied using the Atomic Force Microscope (AFM) and showed that the ZnO membrane has a smooth and uniform surface in composition.